Intrauterine growth restricted rats exercised before and during pregnancy: maternal and perinatal repercussions - Corvino, S. B. [UNESP]; Volpato, G. T. [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Damasceno, D. C. [UNESP] (Hindawi, 2015)
This study aimed at evaluating the effect of swimming before and during pregnancy on rats born with intrauterine growth restriction (IUGR) and their offspring. For this, nondiabetic and streptozotocin-induced severely diabetic (SD) pregnant rats were mated and generated offspring with appropriate (control, C) and small (IUGR) for pregnancy age, respectively. Following that, C and IUGR groups were further distributed into nonexercised control (C), exercised control (Cex), nonexercised IUGR (IUGR), and exercised IUGR (IUGRex). IUGR rats presented lower mating rate than control rats. Regardless of physical exercise IUGR rats presented decreased body weight from birth to lactation. At 90 days of life, IUGR rats presented glucose intolerance. Maternal organ weights were increased and relative adiposity of IUGRex rats was lower than Cex. IUGR and IUGRex offspring presented reduced body weight than C and Cex, respectively. IUGRex dams presented an increased rate of appropriate for pregnancy age newborns. IUGEex male and female offspring relative brain weight was increased compared with Cex. Therefore, swimming before and during pregnancy prevented glucose intolerance, reduced general adiposity, and increased maternal and offspring organ weight in rats, showing the benefit of physical exercise for IUGR rats.